Tobacco control law enforcement in Hangzhou, China: a qualitative study - Meng Wang; Hui Yin; Hongjun Chen; Shuyao He; Zuokun Liu; Jingbo Qi (BMJ Open)
Background The updated version of the Regulation on Smoking Control in Public Places in Hangzhou commenced on 1 January 2019.Objective This study aims to summarise Hangzhou’s municipal-level law enforcement experience and to analyse facilitators and impediments to the implementation of the Regulation.Design Qualitative methods are used in this study.Setting The participants were invited to participate in online interviews.Participants A total of 10 individuals from Hangzhou’s municipal, district and county levels, involved in tobacco control, participated in semistructured interviews employing the grounded theory.Results The primary coding themes of concern to the interviewees were the ‘law enforcement programme’, the ‘law enforcement agencies’ and the ‘law enforcement monitoring’. The secondary coding themes of interest were the ‘role and division of labour’, the ‘inspection procedure’ and the ‘frequency of law enforcement’. The study found that facilitators to the implementation of the tobacco control law in Hangzhou include the incremental enhancement of the coordination mechanism and workflow of joint law enforcement agencies; the balanced administrative enforcement of tobacco control under the guidance of the flexible law enforcement strategy and the institution of law enforcement monitoring based on the Healthy Hangzhou Assessment. Impediments identified include inadequate interfacing and integration of data and platforms related to tobacco control law enforcement; differences in the law enforcement processes among different agencies; understaffing in tobacco control law enforcement agencies represented by non-health departments; and the absence of systematic performance evaluation and incentive mechanisms for routine tobacco control law enforcement.Conclusion Further improvement in the implementation of the tobacco control law is needed in Hangzhou in the future.